1991
DOI: 10.1073/pnas.88.21.9543
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic hydrocarbon responsiveness-receptor agonists generated from indole-3-carbinol in vitro and in vivo: comparisons with 2,3,7,8-tetrachlorodibenzo-p-dioxin.

Abstract: Indole-3-carbinol (13C) is a secondary plant metabolite produced in vegetables of the Brassica genus, including cabbage, cauliflower, and brussels sprouts. I3C is both an anti-initiator and a promoter of carcinogenesis. Consumption of 13C by humans and rodents can lead to marked increases in activities ofcytochrome P-450-dependent monooxygenases and in a variety ofphase II drug-metabolizing enzymes. We have reported previously that the enzyme-inducing activity of 13C is mediated through a mechanism requiring e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
387
1
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 519 publications
(404 citation statements)
references
References 29 publications
12
387
1
4
Order By: Relevance
“…First, DIM, an important metabonate of I3C, which is thought to be at least in part responsible for its chemopreventive efficacy, 24 does not seem to be implicated in the hepatoprotection provided by I3C. This supposition is borne out by the finding that DIM failed to ameliorate any ET-743-induced hepatic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, DIM, an important metabonate of I3C, which is thought to be at least in part responsible for its chemopreventive efficacy, 24 does not seem to be implicated in the hepatoprotection provided by I3C. This supposition is borne out by the finding that DIM failed to ameliorate any ET-743-induced hepatic changes.…”
Section: Discussionmentioning
confidence: 99%
“…24 Therefore, we explored whether DIM might be responsible at least in part for the hepatoprotection afforded by I3C. To that end, I3C was replaced with DIM (0.2% in the diet, w/w) and its ability to protect rat livers against the detrimental activity of ET-743 was studied.…”
Section: Effect Of Diindolylmethane On Hepatotoxicity Of Et-743mentioning
confidence: 99%
“…36 While 3-methylcholanthrene obviously has no potential therapeutic utility, less hazardous agents are available that induce hepatic metabolizing enzymes by the same mechanism. 37,38 Furthermore, the risk of adverse effects associated with the long-term use of these agents may be outweighed by the risk of developing life-threatening kernicteric encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Other acid catalyzed products of I3C likely account for the ability of dietary I3C to markedly reduce the incidence of estrogenresponsive mammary tumors in rodents. Several studies have shown that ICZ binds to the aromatic hydrocarbon (Ah) receptor and induces P450 CYP1A1 gene expression, which can alter estrogen metabolism [18,24,25]. However, at least one of the acid catalyzed products, CTr, is a strong estrogen receptor agonist capable of increasing the proliferation rate of cultured human breast cancer cells [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, at least one of the acid catalyzed products, CTr, is a strong estrogen receptor agonist capable of increasing the proliferation rate of cultured human breast cancer cells [22]. In contrast, I3C has little affinity for either the Ah or estrogen receptors [10,25,26]. Thus, the overall effect of oral I3C may result from a complex balance of the proliferative and anti-proliferative effects of the acid catalyzed products.…”
Section: Introductionmentioning
confidence: 99%